Magnetic resonance imaging T2* of the pancreas value using an online software tool and correlate with T2* value of myocardium and liver among patients with transfusion-dependent thalassemia major - Hoe, Han Guan; Git, Kim-Ann; Loh, C-Khai; Abdul Latiff, Zarina; Hong, Joyce; Abdul Hamid, Hamzaini; Wan Sulaiman, Wan Noor Afzan; Mohd Zaki, Faizah (Frontiers in Radiology, 2022)
Objective: Thalassemic major patients do require lifetime blood transfusions which eventually result in iron accumulation in different organs. We described the usefulness of using MRI T2*imaging values for evaluation of pancreatic iron load in these patients, and we correlated it with MRI T2* haemosiderosis of the myocardium and liver which has been recognized as a non-invasive assessment of iron overload among thalassemic major patients. Materials and Methods: We conducted a cross-sectional study on 39 thalassemic major patients in one of the tertiary university hospitals for a one year period. Demographic data were collected from the patients’ history. MRI T2* of the pancreas, liver and heart were executed on all patients in the same setting. Objective values of iron overload in these organs were obtained using MRI post-processing software from on-line software. Results: Thirty-two (82.1%) patients had pancreatic iron overload including 2 (5.1%) with severe iron overload, and 15 (38.5%) with moderate and mild iron overload, respectively. Nine patients (23.1%) had myocardial iron overload, which included 3 patients (7.7%) who noted to have severe cardiac hemosiderosis. Thirty-seven patients (94.9%) had liver iron overload with 15 (38.5%) who had severe liver hemosiderosis. There was a moderate positive correlation between the relaxation time of pancreas and heart hemosiderosis (r=0.504, P<0.001). No significant correlation found between the relaxation time of the pancreas with the liver and the heart with the liver. Conclusion: Pancreatic hemosiderosis precedes cardiac haemosiderosis, which establishes a basis for initiating earlier iron-chelation therapy for Thalassemia major patients.